UV protection and antimicrobial finish on cotton khadi fabric using a mixture of nanoparticles of zinc oxide and poly-hydroxy-amino methyl silicone. Issue 11 (June 2019) - Kar, Tapas Ranjan; Samanta, Ashis Kumar; Sajid, Mohammed; Kaware, Runali
A different percentage of nanoparticles of zinc oxide dispersed in a newer amino-silicone binder (poly-hydroxy-amino methyl silicone) were applied to bleached cotton khadi (handloom woven from handspun yarns) fabric to impart both ultraviolet protection and an antimicrobial finish in one step using the pad-dry-cure method, instead of using two processes for two different finishes. Amongst the varying dosages of nanoparticles of zinc oxide (1% to 5%) on the weight of fabric dispersed in poly-hydroxy-amino methyl silicone (2–10%) owf, 1% nanoparticles of zinc oxide and 4% poly-hydroxy-amino methyl silicone show ultraviolet protection factor 10 and 93–95% antibacterial reduction, whereas a 4% poly-hydroxy-amino methyl silicone and 5% nanoparticles of zinc oxide combination yields ultraviolet protection factor 20 and 99% antibacterial reduction. Thus, nanoparticles of zinc oxide at the level of 5% application with 4% poly-hydroxy-amino methyl silicone gives the best antimicrobial (99% bacterial reduction) and ultraviolet protection factor value of 20, balanced with 15–20% loss of fabric tenacity. Fourier transform infrared spectroscopy analysis reveals a complex formation between cellulose/oxy-cellulose and poly-hydroxy-amino methyl silicone that embeds nanoparticles of zinc oxide within it. Supporting reaction mechanisms proposed for both energy dispersive spectroscopy and atomic absorption spectrophotometry results further confirm the presence of zinc, potassium, and silicon on the treated cotton fabric. A wash stability test also shows the stability of the antimicrobial treatment for up to five wash cycles with 96% bacterial reduction and retention of ultraviolet protection factor of 15 after five washes. Thus, this single step combining ultraviolet protective and antimicrobial finishing of cotton fabric may be used for eco-fashion garments to protect the human skin from ultraviolet light and microbes alongside its possible uses in medical textiles to protect human body parts.